Inside the yield book : the classic that created the science of bond analysis - Homer, Sidney, 1902-1983.; Leibowitz, Martin L., 1936-; Wiley eBooks (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
A completely updated edition of the guide to modern bond analysis First published in 1972, Inside the Yield Book revolutionized the fixed-income industry and forever altered the way investors looked at bonds. Over forty years later, it remains a standard primer and reference among market professionals. Generations of practitioners, investors, and students have relied on its lucid explanations, and readers needing to delve more deeply have found its explication of key mathematical relationships to be unmatched in clarity and ease of application. This edition updates the widely respected classic with new material from Martin L. Leibowitz. Along the way, it skillfully explains and makes sense of essential mathematical relationships that are basic to an understanding of bonds, annuities, and loans-in fact, any securities or investments that involve compound interest and the determination of present value for future cash flows. The book also includes a new foreword. Contains information that is more instructive, important, and useful than ever for mastering the crucial concepts of time, value, and return Combines the clear fixed-income insights found in the original edition with completely new knowledge to help you navigate today's dynamic market Includes over one hundred pages of new material on the role of bonds within the total portfolio In an era of calculators and computers, some of the important underlying principles covered here are not always grasped thoroughly by market participants. Investors, traders, and analysts who want to sharpen their ability to recall and apply these fundamentals will find Inside the Yield Book the perfect resource.
pt. I. Duration targeting : a new look at bond portfolios (2013 edition) -- pt. II. Some topics that didn't make it into the 1972 edition (2004 edition) -- pt. III. Inside the yield book (original edition).
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Bonds -- United States; Bond market; BUSINESS & ECONOMICS -- Investments & Securities -- Bonds; Bond market; Bonds; United States; Bonds / United States; Bond market; Electronic books